Epstein-Barr virus induced hemophagocytic lymphohistiocytosis in X-linked lymphoproliferative disease - Sankararaman, Senthilkumar (Medknow Publications & Media Pvt Ltd, 2014)
X-linked lymphoproliferative disease (XLP) is a rare, often fatal genetic disorder characterized by extreme vulnerability to Epstein-Barr virus (EBV). EBV-induced hemophagocytic lymphohistiocytosis (HLH) is a known presentation in XLP. In EBV-induced HLH in XLP, the brain imaging findings in the acute phase include a non specific pattern. In this report, we highlight the magnetic resonance imaging and magnetic resonance spectroscopy findings in a child with EBV induced HLH in XLP.